Agency Costs and Asset Management Efficiency Influence the Profitability of Companies Listed on the Market for Alternative Investment (MAI) - Thaneerananon , Arisara (Rajapark Journal, 2024)
This research therefore aims to analyze agent costs, asset management efficiency, firm size, and financial risks that influence the profitability of companies listed on the Market for Alternative Investment (MAI). This research therefore has the objectives of studying and analyzing agency costs, and the efficiency of asset management that influence the profitability of companies listed on the MAI Stock Exchange. This research is quantitatively conducted by collecting data from the MAI Stock Exchange during the years 2021-2023, a total of 556 samples from 181 companies were analyzed by multiple regression analysis. The results found that the ability to manage assets has a positive influence on profitability. Firm size has a positive influence on profitability. And it was found that agency costs have a negative influence on profitability. The ability of the debt-to-equity ratio to have a negative influence on profitability. So asset management and firm size have increased influence on the business’s ability to make increased profits, and as agent costs increase, the debt-to-equity ratio decreases. In addition, the debt-to-equity ratio has decreased, resulting in the business’s ability to make more profits. This research was able to explain 22% of the change in profitability.